Transparência, participação social e mídias sociais na gestão pública: o uso da rede social Facebook na comunicação entre a prefeitura municipal de Curitiba e sua população - Freitas, Jeferson (2017)
With the advent of new technologies and, particularly, with the outbreak of digital platforms, different forms of communication within varied organizational contexts have emerged. Within the sector of public management, technology and digital platforms have been used as a way of providing better communication between the public and the domestic arenas. Transparency and social participation both intertwine with New Public Management, which states that a transparent management allows citizens to engage in social participation within the public planning. For that to happen in an efficient way and become the norm, it’s essential to be aware of and understand the information released. In this specific scenario, this study aimed at analyzing transparency and social participation within the communication between the City Hall of Curitiba and its citizens through the social media platform, Facebook. The study investigated how the communication developed within that social platform tackled both transparency and social participation. The theoretical framework articulated the Theory of Medialization and the use of social media communication in the light of New Public Management. A quantitative and qualitative research based on secondary data available on WEB 2.0 was carried out. The research covers communication from 2013, the year when the city hall released its Facebook page named “Prefs” – up to 2016. Audiovisual and textual contents taken from 17 posts released by “Prefs” were collected and analyzed. For the quantitative stage, evaluation metrics were measured on four affordances: (i) comments on Prefs’ replies; (ii) citizen comments; (iii) popularity; (iv) virality. The qualitative stage was defined by the content analysis of posts grouped into 12 areas of action officially established by the public management of each year. The areas of action were (i) Social care; (ii) Culture; (iii) Education; (iv) Sports; (v) Housing; (vi) Infrastructure; (vii) Youth; (viii) Mobility; (ix) Women; (x) Health; (xi) Public safety; (xii) Seniors. The results of this study demonstrate that both transparency and social participation became meaningful elements within the Facebook communication established by the city hall with its own citizens and those of other cities as well.